ANALISIS KESALAHAN SISWA DENGAN KEMAMPUAN TINGGI DALAM MENYELESAIKAN SOAL NUMERASI BERDASARKAN KEMAMPUAN MATEMATIKA - Nadhiroh, Alik; Yustitia, Via; Hadi, Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Numeracy is a student's ability in counting skills, be it counting lessons, simple counting, and measuring activities that exist in daily life. In addition, numeration skills can be used as capital for students in mastering other subjects. This research aims to describe the types of mistakes that students often make in solving numeracy problems and analyse the relationship between those errors and students' mathematical abilities. The type of research used is a qualitative research subject for class IV students of the Odd semester 2024/2025. The time of the implementation of this research was carried out in the year 2024. Test data collection techniques, interviews and documentation. The technique used in this study is purposive sampling which is used in selecting 3 students as subjects. Subject selection is chosen based on the student's results in doing numeration problems from high, medium and low categories. The instruments in this study used a math ability test and a numeration test. The data analysis methods used are data collection, data condensation, data presentation and drawing conclusions. Based on the results of the research that has been conducted seen from the aspect of mathematical ability, the following are errors from each subject: (1) Subjects with high mathematical ability make 1 type of error, namely errors in understanding the problem (2) Subjects with mathematical ability are making 3 types of errors in understanding the problem, process errors and errors in writing answers (3) Subjects with low mathematical ability make 5 types of process errors, answer writing errors are found in questions number 1 and 2, transformation errors, reading errors. Students' mathematical ability and numeration skills have a highly correlated and positively related relationship which explains that the higher the student's mathematical ability, the higher the student's numeral ability.